Association between COPD and CKD: a systematic review and meta-analysis - Liu, Zexin; Ma, Zhimin; Ding, Chaowei (Frontiers in Public Health, 2024)
ObjectiveChronic obstructive pulmonary disease (COPD) and chronic kidney disease (CKD) are significant global health issues with a well-established association between the two. This study aims to assess the risk of developing CKD in patients with COPD through systematic review and meta-analysis, and to explore the impact of CKD on the prognosis of COPD patients.MethodsA total of 23 studies were included in the analysis, comprising 11 studies on the risk of CKD in patients with COPD, 6 studies on the impact of CKD on the short-term all-cause mortality risk of patients with acute exacerbation of COPD (AECOPD), and 6 studies on the impact of CKD on the long-term all-cause mortality risk of COPD patients. The meta-analysis showed that the risk of developing CKD in COPD patients was significantly increased (OR 1.54, 95% CI: 1.28–1.84), and CKD significantly increased the short-term all-cause mortality risk in AECOPD patients (OR 1.53, 95% CI: 1.44–1.63) as well as the long-term all-cause mortality risk in COPD patients (OR 1.70, 95% CI: 1.35–2.15).ResultsWe searched the PubMed, EMBASE, and Cochrane Library databases in accordance with the PRISMA guidelines, including studies from the inception of the databases through December 31, 2023, to identify research assessing the relationship between COPD and CKD. The quality of the studies was assessed using the Newcastle-Ottawa Scale (NOS). Data were analyzed using either a random effects model or a fixed effects model for the meta-analysis.ConclusionThis study establishes a significant association between COPD and CKD and reveals the adverse impact of CKD on the prognosis of COPD patients, which may provide important guidance for clinical practice.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/.